The integration of industry case-based-environmental sustainability with heutagogy approach in evaluating the thinking skills among technical students - Haryanti Mohd Affandi; Norazlinda Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study evaluated the efficacy of an innovative teaching method framework, which incorporated heutagogical techniques and industrial case-based learning, in boosting the critical thinking abilities of vocational students. Using a pre-and post-test experimental design, 120 students from three Malaysian vocational colleges were randomly assigned to experimental and control groups. The experimental group participated in a three-day environmental sustainability and heutagogy-based educational camp. Pre- and post-test performance was graded using a validated rubric that evaluated analytical, creative, and practical thinking skills. Controlling for pre-test performance, Multivariate Analysis of Covariance (MANCOVA) demonstrated a substantial influence of the heutagogical method on the post-test scores of the students. These findings demonstrate the potential for creative, hands-on teaching techniques, such as heutagogy coupled with industry case-based learning, to improve students’ critical thinking abilities. For even more outstanding results, future studies should examine complex, personalised teaching tactics that consider pupils’ various learning styles. This study highlights the significance of industry-relevant and learner-centred teaching approaches, especially in Technical and Vocational Education and Training (TVET).